2007
DOI: 10.1016/j.neuroimage.2007.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Role of neuronal activity and kinesin on tract tracing by manganese-enhanced MRI (MEMRI)

Abstract: MEMRI offers the exciting possibility of tracing neuronal circuits in living animals by MRI. Here we use the power of mouse genetics and the simplicity of the visual system to test rigorously the parameters affecting Mn 2+ uptake, transport and trans-synaptic tracing. By measuring electrical response to light before and after injection of Mn 2+ into the eye, we determine the dose of Mn 2+ with the least toxicity that can still be imaged by MR at 11.7T. Using mice with genetic retinal blindness, we discover tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
145
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(151 citation statements)
references
References 35 publications
4
145
2
Order By: Relevance
“…Various substances move at different rates independently of the electrical activity within the axons (3,4) and are grouped in fast and slow components with speeds of %4-16 mm/h and 4-250 mm/h, respectively, in the healthy axon, (3,5). The same ''fast'' molecular motors are involved in both fast and slow axonal transport, but during slow axonal transport there are prolonged pauses between periods of movements (6,7).…”
mentioning
confidence: 99%
“…Various substances move at different rates independently of the electrical activity within the axons (3,4) and are grouped in fast and slow components with speeds of %4-16 mm/h and 4-250 mm/h, respectively, in the healthy axon, (3,5). The same ''fast'' molecular motors are involved in both fast and slow axonal transport, but during slow axonal transport there are prolonged pauses between periods of movements (6,7).…”
mentioning
confidence: 99%
“…The toxicity of Mn 2ϩ is well documented. After high doses and after long exposure, Mn 2ϩ induces both systemic and neurological effects (24,25). Thus, MEMRI should be performed with an Mn 2ϩ dose that produces satisfactory tissue contrast without inducing severe toxic effects.…”
mentioning
confidence: 99%
“…However, it has been shown that 50 nmol of Mn 2+ injected into the vitreous body of a mouse eye disturbed neuronal electrophysiology measured in the visual cortex (Bearer et al, 2007). A similar dose (45 nmol of Mn 2+ ) caused degeneration of the dopaminergic ventral tegmental area (VTA) neurons after a direct intracerebral injection in rats (own unpublished data).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
“…However, that study focused on cortical and not midbrain neurons. Furthermore, a signal change measured 24 h after an injection of only a few nmol of Mn 2+ was not detectable by an 11 T MR scanner (Bearer et al, 2007). Therefore, when doses below 10 nmol are used the MR acquisition either takes place directly after the injection (Canals et al, 2008) or requires a scanning time of several hours (Pautler et al, 2003).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation